1996
DOI: 10.1126/science.271.5245.81
|View full text |Cite
|
Sign up to set email alerts
|

Language Comprehension in Language-Learning Impaired Children Improved with Acoustically Modified Speech

Abstract: A speech processing algorithm was developed to create more salient versions of the rapidly changing elements in the acoustic waveform of speech that have been shown to be deficiently processed by language-learning impaired (LLI) children. LLI children received extensive daily training, over a 4-week period, with listening exercises in which all speech was translated into this synthetic form. They also received daily training with computer "games" designed to adaptively drive improvements in temporal processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
639
4
51

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,076 publications
(726 citation statements)
references
References 26 publications
(9 reference statements)
32
639
4
51
Order By: Relevance
“…Many children with reading problems exhibit deficits in the perception of speech sounds (de Weirdt, 1988;Elliott et al, 1989;Watson and Miller, 1993). This has been attributed to inadequate phonological awareness skills and/or difficulties in perceiving brief sounds (including rapid spectral changes) which occur in speech (Golden and Steiner, 1969;Godfrey et al, 1981;Lieberman et al, 1985;Werker and Tees, 1987;Liberman et al, 1989;Reed, 1989;Elbro et al, 1994;Torgesen and Barker, 1995;Kraus et al, 1996;Merzenich et al, 1996;Stark and Heinz, 1996;Tallal et al, 1996;Mody et al, 1997;Schulte-Koerne et al, 1999). Of particular importance for some learning-impaired children is that these perceptual deficits can be absent in quiet, but manifested in noise typical of everyday listening situations (Elliot et al, 1979;Brady et al, 1983;Chermak et al, 1989;Cunningham et al, 2001;Bradlow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many children with reading problems exhibit deficits in the perception of speech sounds (de Weirdt, 1988;Elliott et al, 1989;Watson and Miller, 1993). This has been attributed to inadequate phonological awareness skills and/or difficulties in perceiving brief sounds (including rapid spectral changes) which occur in speech (Golden and Steiner, 1969;Godfrey et al, 1981;Lieberman et al, 1985;Werker and Tees, 1987;Liberman et al, 1989;Reed, 1989;Elbro et al, 1994;Torgesen and Barker, 1995;Kraus et al, 1996;Merzenich et al, 1996;Stark and Heinz, 1996;Tallal et al, 1996;Mody et al, 1997;Schulte-Koerne et al, 1999). Of particular importance for some learning-impaired children is that these perceptual deficits can be absent in quiet, but manifested in noise typical of everyday listening situations (Elliot et al, 1979;Brady et al, 1983;Chermak et al, 1989;Cunningham et al, 2001;Bradlow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available auditory training software programs, incorporating exercises to improve temporal processing and phonological awareness skills, are widely used by learning-impaired children Tallal et al, 1996;Morrison, 1998;Diehl, 1999). The impact of these programs on neurobiological processes associated with auditory perceptual problems is unknown, and the perceptual and cognitive benefits are still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the work of Tallal stands as an alternative to the mainstream phonological focus. Tallal et al (1996) claim that her earlier work on 'language-learning-impaired (LLI) children' has shown that: '[R]ather than deriving from a primarily linguistic or cognitive impairment, the phonological and language difficulties of LLI children may result from a more basic deficit in processing rapidly changing sensory inputs.' (p. 81).…”
Section: The Auditive-deficit Hypothesismentioning
confidence: 99%
“…During the last two or three decades, Tallal and her co-workers have claimed that the phonological deficit found in dyslexics and dysphasics can be explained as a result of auditive anomalies (Tallal & Piercy, 1973, 1974Tallal et al, 1996). For example, Tallal (1984) claims that the phonological deficit is a symptom of an underlying deficit in auditory temporal processing.…”
Section: Symptomsmentioning
confidence: 99%
“…For example, such research has led to the development of programs for reading remediation (e.g. [79]), which have yielded improvements in performance. However, interpreting such results requires control treatments that are equated with the remediation treatments in all ways except those thought to be essential for remediation.…”
Section: Interactions and Integrationsmentioning
confidence: 99%